Protozoan and Helminth Contamination in Ecuadorian Agricultural Products: Dominance of Blastocystis sp. - Luisa Carolina González-Ramírez; Cristian Andrés Quito López; Verónica Carolin Rojano Silva; Ximena del Rocío Robalino Flores; Silvia Paola Monar Basantes; José G. Prato; César Díaz-Godínez; Julio César Carrero (Journal of Parasitology Research)
Foodborne diseases, particularly those caused by parasitic infections, pose significant public health challenges globally, particularly affecting vulnerable populations such as children. In this study, we investigated the parasitic contamination in 773 samples of fruits, vegetables, and leafy greens from Ecuador’s Chimborazo Province. Utilizing a cross-sectional, observational approach, samples were collected from the capital of the Guano canton, Chimborazo Province. The analysis revealed an alarming overall contamination frequency of 74.5%, with leafy greens exhibiting the highest contamination (238/275 [86.5%]), followed by vegetables (130/188 [69.1%]) and fruits (208/310 [67.1%]) (X2=32.793; p<0.0001). Protozoa (71.8%) were four times more prevalent than helminths (16.9%) (X2=471.106; p<0.0001), showing a higher frequency in leafy greens (228/275 [82.9%]) compared to fruits (205/310 [66.1%]) and vegetables (122/188 [64.9%]) (X2=26.113; p<0.0001). In contrast, helminths were more frequently found in vegetables (54/188 [28.7%]) than in leafy greens (49/275 [17.8%]) and fruits (28/310 [9%]) (X2=32.469; p<0.0001). Notably, Blastocystis sp. was the most frequently identified parasite in all types of produce, particularly in fruits (43.5%) and leafy greens (40.7%). These findings underscore the critical need to improve food safety protocols and sanitation practices in agricultural settings to mitigate health risks associated with parasitic infections, especially among children in socioeconomically disadvantaged rural communities.